Pengaruh Kualitas Sumber Daya Manusia Perangkat Desa terhadap Perencanaan, Pelaksanaan, dan Pertanggungjawaban Program Berbasis Dokumen Perencanaan Desa - Ronald Wonmaly; Zainal Abidin Rengifurwarin; Mike J. Rolobessy (MAN 4 Kota Pekanbaru, 2025)
This study investigates the influence of human resource quality of Negeri apparatus on the planning, implementation, and accountability of development programs based on official planning documents in Teon Nila Serua District, Central Maluku Regency. Negeri apparatus are key actors in village governance, translating development priorities into effective planning and reporting. Using a quantitative associative approach, data were collected from 67 respondents via structured questionnaires and analyzed with multiple linear regression. The results show that human resource quality has a significant positive effect on planning accuracy, program implementation, and accountability reporting. The model explains 48.7% of the variation in program management outcomes (R² = 0.487). These findings highlight the need to strengthen Negeri apparatus capacity through targeted training, administrative support, and improved coordination to ensure transparent, accountable, and responsive governance at the village level.